ANALISIS YURIDIS TERHADAP PEMBERIAN DISPENSASI KAWIN DI KANTOR PENGADILAN AGAMA PANGKAJENE KABUPATEN PANGKEP - Ratnawati M; Firman Umar; Mustaring Mustaring (Universitas Negeri Makassar, 2023)
This study aims to find out the reasons why the community applied for a marriage dispensation and to find out what the judges considered in granting and rejecting requests formarriage dispensation at the Pangkajene Religious Court. The data of this study were evaluated through a qualitative descriptive analysis with three stages: reduction, presentation and conclusion. Various data collection methods include observation, interviews and documentation. The results of this study indicate that the reasons people apply for dispensation from marriage are pregnancy before marriage, having had husband and wife relations, arranged marriages as part of the culture of society, dating which causes concern for parents, school dropout factors and economic factors where the parents are no longer able to afford it. provide for his son. The judge's considerations in granting and rejecting the application for a marriage dispensation have been regulated in PERMA Number 5 of 2019. The request for a marriage dispensation was granted by the judge on the following considerations: 1) The prospective bride is pregnant; 2) Both prospective bride and groom have had a relationship like husband and wife; 3) Has matured physically; 4) Able from an economic point of view. The judge's considerations in rejecting the request for a Marriage Dispensation are: 1) The reasons put forward are incomplete and the evidence brought to court is imperfect; 2) Legal facts were found at trial where there was a discrepancy between the statements of the applicant/children of the applicant, the prospective husband/wife and the parents of the prospective husband/wife and the statements of the witnesses that were between one another. The judge in deciding the application for marriage dispensation still pays attention to the benefits and harms for the survival of the child.Studi ini bertujuan untuk mengetahui alasan masyarakat mengajukan Dispensasi Kawin dan untuk mengetahui apa yang menjadi pertimbangan hakim dalam mengabulkan dan menolak permohonan Dispensasi Kawin di Pengadilan Agama Pangkajene. Data studi ini dievaluasi melalui analisis deskriptif kualitatif dengan tiga tahap yaitu tahap : reduksi, penyajian serta penarikan kesimpulan. Berbagai metode pengumpulan data meliputi observasi, wawancara dan dokumentasi. Hasil studi ini menunjukkan bahwa alasan masyarakat mengajukan permohonan dispensasi kawin, yaitu hamil sebelum menikah, telah melakukan hubungan suami istri, perjodohan sebagai bagian darii budaya masyarakat, pacaran yang menimbulkan kekhawatiran orang tua, factor putus sekolah dan factor ekonomi dimana orang tuanya sudah tidak mampu lagi menafkahi anaknya. Pertimbangan hakim dalam mengabulkan dan menolak permohonan Dispensasi Kawin telah diatur dalam PERMA Nomor 5 tahun 2019. Pemohonan dispensasi kawin dikabulkan oleh hakim atas pertimbangan yakni : 1) Calon mempelai Wanita telah hamil; 2)Kedua calon mempelai telah melakukan hubungan layaknya suami istri; 3)Telah matang secara fisiknya; 4) Mampu dari segi ekonomi. Pertimbangan hakim dalam menolak permohonan Dispensasi Kawin yaitu : 1) Alasan yang diajukan kurang lengkap dan bukti yang dibawa kepersidangan tidak sempurna; 2) Ditemukannya fakta-fakta hukum di persidangan adanya ketidak sesuaian keterangan pemohon/anak pemohon, calon suami/istri dan orang tua calon suami/istri dan keterangan saksi-saksi yang antara satu dengan yang lainnya. Hakim dalam memutuskan permohonan dispensasi kawin tetap memperhatikan mashlahat dan mudaratnya bagi kelangsungan hidup anak.